Three Worlds of Old-Age Decommodification? A Comparative Analysis of Old-Age Support and Inequality Using the Luxembourg Income Study - Brian Gran (Luxembourg Income Study (LIS), 1993)
The author uses LIS data to test, on an individual level, Esping-Andersen's hypothesis that the three political strategies he conceived in The Three Worlds of Welfare Capitalism (1990) furnish homogenous old-age decommodification levels. He finds not only that the levels of decommodification are more heterogeneous than the thesis suggests but also that some systems generate inequality by providing higher levels of decommodification to some cultural groups.
Keywords: 330